Enhanced prostanoid release from monocytes of patients with rheumatoid arthritis and active systemic lupus erythematosus. Issue 7 (July 1985) - Seitz, M; Hunstein, W
Abstract : In patients with rheumatoid arthritis high levels of prostaglandin E1 have been found in the joint fluid, and its increased production by adherent synovial cells and macrophages clearly supports the notion that this arachidonic acid metabolite is involved in the pathology of the disease. Besides its known inflammatory qualities and the suppressive effects on various lymphocyte functions prostaglandin E2 has proved to be an essential cofactor in the secretion of the lymphokine osteoclast activating factor. In this study we have discovered an enhanced release of prostaglandin E1 and thromboxane B2 from a subpopulation of blood monocytes from patients with rheumatoid arthritis and active systemic lupus erythematosus. No correlation between prostanoid release from monocytes and inflammatory activity of the disease was found. However, even monocytes from patients with early stage or mild inflammatory activity displayed a 'stimulated' arachidonic acid metabolism. In contrast only patients with active systemic lupus erythematosus showed in this respect comparable secretory activity or monocytes. Our findings may point to a possible pathogenic role of prostanoids in rheumatoid arthritis, which may also have some implication for the early diagnosis of this disease and for its differentiation from other chronic inflammatory rheumatic conditions.